THE EFFECT OF USING TIME TOKEN ARENDS TOWARDS STUDENTS’ SPEAKING SKILL; A CASE OF SMA NEGERI 1 KONTUKOWUNA - Suharni, Sitti; Nurnia, Nurnia; Agustina, Sitti (Journal of Teaching of English, 2020)
This study was conducted to examine whether there is or not any significant effect of Time Token Arends towards students’ speaking skill at the second year students’ of SMA Negeri 1 Kontukowuna. This research was conducted in pre-experimental research design. The population of this study was all students of SMA Negeri 1 Kontukowuna with the total of the students were 193 students, while the subject of this research was the second grade science program (XI IPA1 class) which consists of 23 students. The data of this research were collected by giving pre-test and post-test to students in the form of oral test related to the topic of report text. The data were analyzed by using SPSS 16.0 version (descriptive analysis and inferential statistics). As for testing the hypothesis, the researcher used t-test (paired sample t-test) which was calculated through SPSS 16,0. The result showed that there was a significant effect of time token technique towards students’ speaking skill at the second year students of SMA Negeri 1 Kontukowuna in terms of accuracy and fluency. It can be seen from the mean score of post-test was 55,22, while the mean score of pre-test was 31,96. In order to prove the hypothesis, the researcher took the conclusion by comparing between the value of Sig (2 tailed) with the significance α value. It showed that the value of Sig (2 tailed) was 0.000 while the significance α value was 0.05. So, it can be concluded that the value of Sig (2 tailed) was lower than the significance α value (0.000 < 0.05). In other words, (H1) was accepted. Besides, the successful improving of students’ speaking skill at the students of XI IPA1 class as the subject of this study did not happen directly without any supporting factors, such as students’ motivation in learning English, students’ intelligence, an interesting topic and a group work activity.